Seasons of Supervision: Reflections on Three Decades of Supervision in Counsellor Education - Jevne, Ronna; Sawatzky, Don; Paré, David (Canadian Journal of Counselling and Psychotherapy, 2007)
This article documents a thematic retrospective of counsellor supervision from two of Canada’s most experienced counsellor educators/supervisors, based at the University of Alberta. Guided by prominent motifs in the counselling literature, the third author invited his colleagues to reflect in an interview on themes and issues they faced during their extensive experience supervising counsellors in university-based counsellor education programs. The article concludes with speculations about future directions in counsellor supervision and in their own practices.